2020
DOI: 10.3390/ijms22010196
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Its Derivatives as Theranostic Agents in Alzheimer’s Disease: The Implication of Nanotechnology

Abstract: Curcumin is a polyphenolic natural compound with diverse and attractive biological properties, which may prevent or ameliorate pathological processes underlying age-related cognitive decline, Alzheimer’s disease (AD), dementia, or mode disorders. AD is a chronic neurodegenerative disorder that is known as one of the rapidly growing diseases, especially in the elderly population. Moreover, being the eminent cause of dementia, posing problems for families, societies as well a severe burden on the economy. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 173 publications
0
43
0
Order By: Relevance
“…Among different kinds of dementia, AD is the most common [55], and it contributes to 60-80% of dementia cases [56]. It is one of the rapidly growing brain diseases [13] and it has been reported that AD and other types of dementia represent the 5th most prominent reason for deaths around the globe. Around 50 million people suffer from dementia, and this is expected to double by 2030, and triple by 2050.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Among different kinds of dementia, AD is the most common [55], and it contributes to 60-80% of dementia cases [56]. It is one of the rapidly growing brain diseases [13] and it has been reported that AD and other types of dementia represent the 5th most prominent reason for deaths around the globe. Around 50 million people suffer from dementia, and this is expected to double by 2030, and triple by 2050.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Different epidemiological studies suggest a strong correlation among lifestyle-related factors, diet, and the onset and consolidation of AD and other kinds of dementia [13]. Studies have reported that nutritional interventions might be helpful to mitigate or delay the risk of cognitive impairment, AD and other non-psychiatric comorbidities.…”
Section: Diet and Food Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition it exerts antioxidant and anti-inflammatory properties. It may have many therapeutic effects [2,3], having exhibited antitumor, chemosensitizing, hepatoprotective, lipid-modifying, and neuroprotective effects [4]. Nevertheless, wellreported in vivo pharmacological activities of curcumin are limited by its poor solubility, bioavailability, and pharmacokinetic profile.…”
Section: Introductionmentioning
confidence: 99%